Povodom jedne knjige / On the occasion of a Book - Filandra, Šaćir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text is a review of a book by Xavier Bougarel: Islam and Nationhood in Bosnia-Herzegovina: Surviving Empires, Sarajevo: Association for Modern History, 2020.